2007
DOI: 10.1039/b707768h
|View full text |Cite|
|
Sign up to set email alerts
|

Dual aromatase–sulfatase inhibitors based on the anastrozole template: synthesis, in vitro SAR, molecular modelling and in vivo activity

Abstract: The synthesis and biological evaluation of a series of novel Dual Aromatase-Sulfatase Inhibitors (DASIs) are described. It is postulated that dual inhibition of the aromatase and steroid sulfatase enzymes, both responsible for the biosynthesis of oestrogens, will be beneficial in the treatment of hormone-dependent breast cancer. The compounds are based upon the Anastrozole aromatase inhibitor template which, while maintaining the haem ligating triazole moiety crucial for enzyme inhibition, was modified to incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…One obvious route to take would be to repeat the two aforementioned strategies for designing a DASI and apply them to other reported aromatase and STS inhibitors. However, repetitive application of the same strategies lacks some novelty and so pursuing a new design approach seemed more desirable and challenging .On reviewing computational docking studies of leading DASIs and other related molecules performed with a homology model of aromatase, 19,23,25 we noticed that the molecules docked in different orientations with unoccupied space available within the enzyme site. This observation suggested that further interactions with available amino acid residues might be exploited in principle if additional functionality could be built into the docked molecule in a complementary manner.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…One obvious route to take would be to repeat the two aforementioned strategies for designing a DASI and apply them to other reported aromatase and STS inhibitors. However, repetitive application of the same strategies lacks some novelty and so pursuing a new design approach seemed more desirable and challenging .On reviewing computational docking studies of leading DASIs and other related molecules performed with a homology model of aromatase, 19,23,25 we noticed that the molecules docked in different orientations with unoccupied space available within the enzyme site. This observation suggested that further interactions with available amino acid residues might be exploited in principle if additional functionality could be built into the docked molecule in a complementary manner.…”
mentioning
confidence: 99%
“…On reviewing computational docking studies of leading DASIs and other related molecules performed with a homology model of aromatase, 19,23,25 we noticed that the molecules docked in different orientations with unoccupied space available within the enzyme site. This observation suggested that further interactions with available amino acid residues might be exploited in principle if additional functionality could be built into the docked molecule in a complementary manner.…”
mentioning
confidence: 99%
See 3 more Smart Citations